Upaya Peningkatan Konsumsi Gemar Makan Ikan Di Desa Sebayan: Efforts To Increase Consumption Of Fish Eating In Sebayan Village - Yogi, Yogi (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Fish is the second provider of animal protein after meat, milk, and eggs. The decline in fish consumption in the community is the focus of a serious problem at this time, where fish consumption is very important. Community service activities aim to increase the importance of eating fish and the benefits of eating fish for the community. The activities carried out are one of the efforts to provide understanding to the public about the importance of consumption like to eat fish. This activity will take place in November 2023 in Sebayan Village, Sambas District, Sambas Regency. The number of people who attended this activity was 65 respondents, consisting of 53 women and 12 men. From the questionnaire data, around 35.4% or 23 respondents stated that there were special obstacles experienced when consuming fish. The activities carried out went well without any obstacles, and the enthusiasm of the community for the presentation of the material delivered by students was quite high. We hope that by eating fish, people can adopt a healthy lifestyle.